Competition Among Gardnerella Subgroups From the Human Vaginal Microbiome - Khan, Salahuddin; Voordouw, Maarten J.; Hill, Janet E. (Frontiers in Cellular and Infection Microbiology, 2019)
Gardnerella spp. are hallmarks of bacterial vaginosis, a clinically significant dysbiosis of the vaginal microbiome. Gardnerella has four subgroups (A, B, C and D) based on cpn60 sequences. Multiple subgroups are often detected in individual women, and interactions between these subgroups are expected to influence their population dynamics and associated signs and symptoms of bacterial vaginosis. In the present study, contact-independent and contact-dependent interactions between the four Gardnerella subgroups were investigated in vitro. The cell free supernatants of mono- and co-cultures had no effect on growth rates of the Gardnerella subgroups suggesting that there are no contact-independent interactions (and no contest competition). For contact-dependent interactions, mixed communities of 2, 3 or 4 subgroups were created and the initial (0 h) and final population sizes (48 h) were quantified using subgroup-specific PCR. Compared to the null hypothesis of additive interactions, most (69.3%) of the mixed communities exhibited competition (p < 0.0001). Competition reduced the growth rates of subgroups A, B and C. In contrast, the growth rate of subgroup D increased in the presence of the other subgroups (p < 0.0001). All subgroups were able to form biofilm alone and in mixed communities. Our study suggests that there is scramble competition among Gardnerella subgroups, which likely contributes to the observed distributions of Gardnerella spp. in vaginal microbiomes and the formation of the multispecies biofilms characteristic of bacterial vaginosis.